Effects of Tissue-engineered Bone by Coculture of Adipose-derived Stem Cells and Vascular Endothelial Cells on Host Immune Status. Issue 6 (December 2021) - Wang, Fuke; Yang, Guiran; Xiao, Yu; He, Chuan; Cai, Guofeng; Song, En; Li, Yanlin
Abstract : Aim: The study aimed to explore the effects of tissue-engineered bone constructed with partially deproteinized biologic bone (PDPBB) and coculture of adipose-derived stem cells (ADSCs) and vascular endothelial cells (VECs) on host immune status, providing a very useful clue for the future development of bone engineering. Methods: Tissue-engineered bones constructed by PDPBB and ADSCs, VECs or coculture of them were implanted into the muscle bag of bilateral femurs of Sprague-Dawley rats. Partially deproteinized biologic bone alone and blank control were also implanted. After transplantation, the proliferation of implanted seed cells in tissue-engineered bones was labeled by bromodeoxyuridine staining. Moreover, the changes of T-lymphocyte subpopulations, including CD3 + CD4+ and CD3 + CD8+ in peripheral blood were then detected using flow cytometry to analyze the immune rejection of tissue-engineered bone implantation based on peripheral blood CD4/CD8 ratios. Results: After transplantation, the proliferation of implanted seed cells was observed in tissue-engineered bones of different groups. At different time points after transplantation, the CD4+/CD8+ ratio in peripheral blood of PDPBB + ADSCs, PDPBB + coculture, and blank control groups did not exhibit significant change. Although the CD4+/CD8+ ratio in peripheral blood of PDPBB + VECs group was significantly higher than other group at 1 week after transplantation, that of PDPBB + VECs and PDPBB + coculture group was significantly decreased at 8 week after transplantation compared with that of blank control group. Conclusions: Our results indicated that there was no significant immune rejection after transplantation of tissue-engineered bone constructed with PDPBB and coculture of ADSCs and VECs as seed cells.